Thermal unrest of a fumarolic field tracked using VIIRS imaging bands: The case of La fossa crater (Vulcano Island, Italy) - Coppola, D.; Laiolo, M.; Campus, A.; Massimetti, F. (Frontiers in Earth Science, 2022)
Detecting precursory signals before an eruption is one of the main objectives of applied volcanology. Among these signals, the variation of the emitted heat flux is certainly an important indicator of a state of disequilibrium within the magmatic system. Here we report the results of a detailed analysis of VIIRS (Visible Infrared Imaging Radiometer Suite) imaging bands (at 375 m spatial resolution) focused on measuring the Volcanic Radiative Power (VRP) emitted by the fumarole field of La Fossa crater (Vulcano Island, Italy) over the past decade (2012–2022). The analysis reveals that the long-term, steady-state VRP (baseline ∼0.17 MW) was perturbed in 2020–2021 when a prolonged period of lower than normal (<-2σ) radiant flux preceded the major unrest phase that began in mid-September 2021. By early October the anomalous VRP had peaked at ∼1.2 MW (6–8 times the baseline) then started to gradually decline in the following months. A subsequent thermal pulse was recorded in May–July 2022 and was accompanied by a period of seawater discoloration that affected the Baia di Levante (a shallow sea bay ∼1.4 km north of La Fossa crater). The concomitance of these phenomena suggests the occurrence of a second pressurization phase driven by the arrival of deep magmatic fluids within both the central and distal degassing fumarolic zones. These results provide a complementary, important contribution to the understanding of the unrest of La Fossa crater and highlight the potential of VIIRS in detecting pre-eruptive signals at other poorly-monitored volcanoes characterized by high-temperature fumarolic activity.